Differential effects of tumor-platelet interaction in vitro and in vivo in glioblastoma - Brockmann, Marc Alexander; Bender, Birte; Plaxina, Elena; Nölte, Ingo; Erber, Ralf; Lamszus, Katrin; Groden, Christoph; Schilling, Lothar (Journal of neuro-oncology, 2011)
An elevated platelet count is considered an independent predictor of short survival in glioblastoma and various other tumor entities. Prothrombotic activity of the tumor microcirculation resulting in platelet activation and release of cytokines from activated platelets has been suggested to play a role. This study was designed to analyze the effects of platelet-released cytokines on glioblastoma and endothelial cell proliferation and migration in vitro, and the influence of platelet count on glioblastoma growth and angiogenesis in vivo. In cultured human glioblastoma, umbilical cord and cerebral microvascular endothelial cells platelet-released cytokines significantly stimulated proliferation and migration as well as sprouting and formation of capillary-like structures. In vivo, glioblastoma cells were implanted in mice followed by platelet depletion starting 1 or 8 days later. Tumor volume, proliferative index, and vessel density analyzed 14 days after engraftment did not differ between animals with a normal and a low platelet count. Likewise, no effect of platelet depletion over 20 days upon the volume of intracerebrally growing tumors was observed in mice. Additionally, proliferative activity and vessel density determined in tumor samples from patients operated upon glioblastoma did not show any correlation with the patients’ preoperative platelet count. Thus, we conclude that distinct proliferation- and chemotaxis-stimulating effects of platelet-derived cytokines can be achieved in vitro, while the platelet count does not exert a major influence on tumor growth and tumor angiogenesis in GBM in vivo.